The Problem of Early-Age Marriage in Afghanistan - Osman Özkul; Nabila Shaheedmal Omari (Journal of Economy Culture and Society)
Early marriage is an ongoing problem in Afghanistan, as is the case in many other countries around the world. This situation has also led to many social, legal, and moral problems. In this study, as a result of the statistical analysis obtained from the surveys, it is understood that the phenomenon of early marriage in Afghanistan continues to be a widespread cultural issue. However, in Afghanistan, it is difficult to say whether there are sufficient sociological studies on the causes and consequences of this problem. Accordingly, elements that demonstrate the originality of our research and some of the causes and results that may contribute to the literature are indicated as results and recommendations. Among the main causes of early marriages in Afghanistan are poverty, pressure from parents, the economic situation, education level, and traditional cultural values. In addition, findings from the interviews show that environmental pressure is very strong. As can be seen in some examples, marriage candidates feel obliged to accept early marriage because they feel unable to deal with oppression. While the impact of the ceremonial and tribal phenomena in the region has weakened, the influence of the tribal structure in the region continues to be seen.